A survey on Mycobacterium ulcerans in Mosquitoes and March flies captured from endemic areas of Northern Queensland, Australia. - Avishek Singh; William John Hannan McBride; Brenda Govan; Mark Pearson; Scott A Ritchie (Public Library of Science (PLoS), 2019)
Mycobacterium ulcerans is the causative agent of Buruli ulcer (BU). This nontuberculous mycobacterial infection has been reported in 34 countries worldwide. In Australia, the majority of cases of BU have been recorded in coastal Victoria and the Mossman-Daintree areas of north Queensland. Mosquitoes have been postulated as a vector of M. ulcerans in Victoria, however the specific mode of transmission of this disease is still far from being well understood. In the current study, we trapped and analysed 16,900 (allocated to 845 pools) mosquitoes and 296 March flies from the endemic areas of north Queensland to examine for the presence of M. ulcerans DNA by polymerase chain reaction. Seven of 845 pools of mosquitoes were positive on screening using the IS2404 PCR target (maximum likelihood estimate 0.4/1,000). M. ulcerans DNA was detected from one pool of mosquitoes from which all three PCR targets: IS2404, IS2606 and the ketoreductase B domain of mycolactone polyketide synthase gene were detected. None of the March fly samples were positive for the presence of M. ulcerans DNA.